Incremental long-term benefit of drug therapies for chronic obstructive pulmonary disease in quality of life but not mortality: a network meta-analysis - Qiong Pan; Jiongzhou Sun; Shiyuan Gao; Zian Liu; Yiwen Huang; Yixin Lian (Archives of Medical Science)
Introduction The latest evidence revealed that dupilumab, an interleukin-4 (IL-4) and interleukin-13 (IL-13) blocker, significantly reduces the exacerbation risk in patients with chronic obstructive pulmonary disease (COPD). The efficacy of dupilumab compared with conventional inhaled drugs remains incompletely determined. This study aimed to investigate the comparative efficacy of dupilumab and conventional inhaled drugs in patients with stable COPD.